COVID-19 Pandemic: Impact on psychiatric care in the United States. (July 2020) - Bojdani, Ermal; Rajagopalan, Aishwarya; Chen, Anderson; Gearin, Priya; Olcott, William; Shankar, Vikram; Cloutier, Alesia; Solomon, Haley; Naqvi, Nida Z.; Batty, Nicolas; Festin, Fe Erlita D.; Tahera, Dil; et al.
Highlights: The COVID-19 pandemic has affected the provision of psychiatric care in the US across all settings. The COVID-19 pandemic has affected the US psychiatry physician by raising personal, financial, and ethical concerns. The COVID-19 pandemic has changed the way medical students and residents learn; the many changes also represent an opportunity for evaluation and innovation that will better prepare us for the next threat to the commonweal. Abstract: The World Health Organization declared the coronavirus outbreak a pandemic on March 11, 2020. Infection by the SARS-CoV2 virus leads to the COVID-19 disease which can be fatal, especially in older patients with medical co-morbidities. The impact to the US healthcare system has been disruptive, and the way healthcare services are provided has changed drastically. Here, we present a compilation of the impact of the COVID-19 pandemic on psychiatric care in the US, in the various settings: outpatient, emergency room, inpatient units, consultation services, and the community. We further present effects seen on psychiatric physicians in the setting of new and constantly evolving protocols where adjustment and flexibility have become the norm, training of residents, leading a team of professionals with different expertise, conducting clinical research, and ethical considerations. The purpose of this paper is to provide examples of "how to" processes based on our current front-line experiences and research to practicing psychiatrists and mental health clinicians, inform practitioners about national guidelines affecting psychiatric care during the pandemic, and inform health care policy makers and health care systems about the challenges and continued needs of financial and administrative support for psychiatric physicians and mental health systems.